The Role of Leadership in the Formation and Functioning of the Organizational Management System - Lishchynskyi, M. P. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2025)
The article thoroughly investigates the key features and strategic role of leadership within the contemporary organizational management system. Based on a critical analysis of scientific literature, various approaches to the interpretation of the essence of leadership are summarized and systematized, which allowed for a clear definition of its content characteristics and an analysis of its basic structural components. Particular attention is paid to demonstrating the critical significance of leadership in ensuring the effectiveness and efficiency of the entire management system. It is argued that the absence of an effective leader or the weakness of leadership functions directly leads to a negative impact on the execution of management functions, complicates decision-making processes, and makes the achievement of desired final organizational results impossible. In the rapidly changing, brittle, non-linear, and incomprehensible BANI world (Brittle, Anxious, Nonlinear, Incomprehensible), the expediency and advantages of utilizing the transformational leadership style are substantiated. This style is considered the most adaptive tool for managing change and enhancing resilience. The paper identifies and details the key qualities that a modern transformational leader must possess for successful navigation in an unstable environment. It is concluded that modern management sets new demands for senior staff, emphasizing that managers must possess not only high professional and technical competencies but also developed leadership qualities, which are a necessary condition for the full realization of managerial potential and the assurance of the organization’s strategic success.